GLOBAL TRENDS IN WORKPLACE DEVIANCE RESEARCH: A BIBLIOMETRIC ANALYSIS (2015 – 2025) - Ruslan, Mohd Sufian; Abdul Wahat, Nor Wahiza; Ismail, Ismi Arif; Ismail, Suriani (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This bibliometric analysis examines global trends in workplace deviance research, a domain tied to organizational effectiveness through links to misconduct, incivility, and withdrawal behaviors. Despite rapid growth, the literature remains diffuse, which constrains cumulative theory development and application. The study maps key trends, influential contributors, themes, and collaboration structures. A Scopus advanced search using the terms workplace deviance and Counterproductive Work Behavior (CWB) identified 1,624 peer-reviewed records from 2015 to 2025. Descriptive statistics and graphs were produced with Scopus Analyzer, records were cleaned and harmonized in OpenRefine, and VOSviewer was used to model keyword co-occurrence and co-authorship by country networks. Output rose steadily from 2015 and accelerated after 2020, peaking in 2024, with 2025 showing strong partial-year activity. The United States and China lead by volume, followed by Pakistan, India, the United Kingdom, Canada, Germany, Australia, Malaysia, and the Netherlands. Themes centre on CWB, organizational justice, leadership styles, abusive supervision, knowledge hiding, cyberloafing, psychological contract breach, and crisis-related contexts. Collaboration networks show dense hubs in North America and Asia with growing ties across South and Southeast Asia. Implications point to strengthening ethical climate, fair procedures, leadership capability, and norms for digital conduct, with attention to knowledge hiding and related knowledge management behaviors associated with retaliation and withdrawal. Overall, the study delivers an integrated and current map of the field, clarifies intellectual anchors, highlights connectors across individual, relational, and organizational mechanisms, and outlines fronts for replication and intervention. It offers a robust reference point for future empirical and conceptual work and supports evidence-informed strategy in organizational settings.